ANTIFUNGAL ACTIVITY OF N-HEXANE EXTRACT FROM Chaetoceros calcitrans AGAINST Candida sp. - Rachmawati, Firdha; Naully, Patricia Gita; Kania, Prina Puspa; Pasha, Delia Ayu (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Skin infections caused by Candida albicans and Candida krusei pose a serious health issue. One major concern regarding these infections is the resistance to antifungal drugs, highlighting the need for natural antifungals. Chaetoceros calcitrans, a microalgae, is known to contain natural antimicrobial compounds. This study aims to evaluate the antifungal potential of C. calcitrans n-hexane extract against both pathogens. The antifungal activity was tested using the diffusion method. The results indicated that the extract at a concentration of 100 mg mL⁻¹ inhibited the growth of C. albicans and C. krusei, showing the highest inhibition zones of 10.3 ± 0.9 mm and 9 ± 1.4 mm, respectively. GC-MS analysis revealed that the C. calcitrans extract contains antifungal compounds, including 2-Butyl-1-hexyloctahydro-1H-indene, at a concentration of 30.72%. Therefore, it can be concluded that C. calcitrans extract possesses antifungal activity and has potential as a drug candidate for fungal skin infections.